- All categories
- Pre-Algebra Answers (11,956)
- Algebra 1 Answers (24,294)
- Algebra 2 Answers (10,079)
- Geometry Answers (4,871)
- Trigonometry Answers (2,497)
- Calculus Answers (5,576)
- Statistics Answers (2,837)
- Word Problem Answers (9,135)
- Other Math Topics (5,435)

3x - 5y = 10 --- (2)

From (1), we have:

x = -7y + 12 --- (3)

Substituting (3) into (2), we will get:

3(-7y + 12) - 5y = 10

-21y + 36 - 5y = 10

-21y - 5y = 10 - 36

-26y = -26

y = -26 / -26

y = 1

Substituting y = 1 into (3), we will get:

x = -7(1) + 12

x = -7 + 12

x = 5

Hence, x = 5 and y = 1.

...